FRAGMENTS OF MEMORY IN RESIDENTIAL INTERIOR ARCHITECTURE - Martha, Loukia (Design/Arts/Culture, 2023)
The present paper tackles the concept of memory as a compositional tool employed in the architectural spatialization process. More specifically, it focuses on residential interior architecture in the work of Greek architect Takis Marthas, placing special emphasis on the conjunction of tradition and Modernism, a binary vividly captured in the architecture and visual arts of the 1930s, to which Marthas belongs. In Marthas’ oeuvre, design and composition are locked in a dialectical relationship by way of cross-pollination, juxtaposition, complementarity, or the introduction of intact fragments of memory into space. Marthas’ architectural style could thus be construed as an attempt of combining the past and the present in the form of a creative process whereby elements–mental or material–are drawn from diverse places and historical periods, only to be repurposed and integrated into a unified whole, retaining their autonomy and alluding to a hybrid architectural model. As far as the composition of the residence is concerned, memory is conveyed through images of the past rendered either as an integral spatial transfer or as mental and material architectural constructions, material elements, textures and colour. These spatial elements evoke and restore images and sensations of the past. Within the architectural creation of the residence, compositional gestures linked with memory can be freely expressed, connecting the past and the present, architecture and place, as well as bringing together the space and users/residents’ personal experiences. Fraught with a number of tensions typical of the 1930s generation, such as the abovementioned attempt to bring together the past and the present, but also to pursue Greekness through both references to antiquity and references to Greek folklore tradition, Marthas’ oeuvre is adumbrated by using residential works as well as written and oral testimonies dating from the 1930s-1960s as methodological tools.